2015
DOI: 10.1080/15384101.2015.1084445
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CDK6 in cancer: State of the art and new insights

Abstract: Cyclin-dependent kinase 6 (CDK6) plays a vital role in regulating the progression of the cell cycle. More recently, CDK6 has also been shown to have a transcriptional role in tumor angiogenesis. Up-regulated CDK6 activity is associated with the development of several types of cancers. While CDK6 is over-expressed in cancer cells, it has a low detectable level in non-cancerous cells and CDK6-null mice develop normally, suggesting a specific oncogenic role of CDK6, and that its inhibition may represent an ideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 120 publications
(146 reference statements)
2
87
0
Order By: Relevance
“…CDK6 upregulation is found in many cancers, including lymphoma, leukemia, bladder cancer, pancreatic cancer, and prostate cancer, as has been reviewed elsewhere. [104] In the brain, increased CDK6 expression can be found in malignant glioma and medulloblastoma. [105][106][107] CDK6 expression in gliomas increases with higher tumor grade and is correlated with a worse prognosis.…”
Section: Cdk6 Is Mutated In Primary Microcephaly and Upregulated In Gmentioning
confidence: 99%
“…CDK6 upregulation is found in many cancers, including lymphoma, leukemia, bladder cancer, pancreatic cancer, and prostate cancer, as has been reviewed elsewhere. [104] In the brain, increased CDK6 expression can be found in malignant glioma and medulloblastoma. [105][106][107] CDK6 expression in gliomas increases with higher tumor grade and is correlated with a worse prognosis.…”
Section: Cdk6 Is Mutated In Primary Microcephaly and Upregulated In Gmentioning
confidence: 99%
“…The above results of the cell cycle assay showed that HOST2 regulated the G 1 /S phase in cells. Through a literature review, it was noted that CDK6 is a major G 0 /G 1 checkpoint regulator and frequently deregulated in cancer cells (27); the expression of CDK6 has been associated with poor survival outcomes and is considered to be a promising therapeutic target for TNBC (28). The results suggested that CDK6 was a key regulator in the G 1 /S phase and is pivotal in the progression of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Among all the members, CDK1, CDK2, CDK4 and CDK6 are implicated in cell cycle regulation while CDKs7‐11 are relevant to transcription (Malumbres & Barbacid, ). The enzymatic activity of CDKs can be stimulated by binding to cyclins and the deregulation of this function is a hallmark of several diseases, including cancer (Tadesse, Yu, Kumarasiri, Le, & Wang, ). Previous research has elucidated that the disorder of CDKs may lead to the malignant proliferation of tumor cells and tumorigenesis (Malumbres & Barbacid, ; Tadesse et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic activity of CDKs can be stimulated by binding to cyclins and the deregulation of this function is a hallmark of several diseases, including cancer (Tadesse, Yu, Kumarasiri, Le, & Wang, ). Previous research has elucidated that the disorder of CDKs may lead to the malignant proliferation of tumor cells and tumorigenesis (Malumbres & Barbacid, ; Tadesse et al, ). Cyclin‐dependent kinase 6 (CDK6) is a member of CDK family, which has been identified not only as a CDK but a transcriptional regulator (Kollmann et al, ; Uras et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation